Relationship between weaning weight and the productive performance of fattening lambs in raised pens - Muñoz-Osorio, Germani Adrián (2022)
The aim of the present study was to evaluate the effect of weaning weight on the productive performance of fattening lambs in raised pens. Data from 932 lambs from one farm over a period of two years were analyzed. The statistical model included the fixed effects of weaning weight (<11, 12-14, 15-17, >18 kg), year (2012 and 2013), season of the year (rainy, dry and northern winds) and simple significant interactions of year × season and the residual error, NID (0, σ2e) on average daily weight gain (GDP, g/d), final weight (PF, kg) and fattening period (PE, days). Weaning weight affected all the response variables evaluated (p<0.05). The weaned lambs between 12-14, 15-17 and >18 kg had a similar GDP, and in turn obtained a higher GDP than the weaned lambs with lower weight (<11 kg; p<0.05). The PF was similar for lambs weaned at 15-17 and >18 kg but higher than that obtained by lambs weaned at <11 kg (p<0.05). The PE was different (p<0.05) for each group of weaning weight, being greater the lower the weaning weight. In conclusion, weaning weight is a factor that affects the GDP, PF and PE of lambs in raised pens.